Pengaruh Kredibilitas Bintang Iklan dan Kredibilitas Merek Terhadap Loyalitas Pengguna Sepeda Motor Yamaha - Putra, Made Adi; Warmika, I Gede Ketut (E-Jurnal Manajemen, 2014)
This research aims to know the influence of endorser credibility and brand credibility to the loyalty of  Yamaha's motorcycle users in Denpasar city. Quantitative approaches in the study of associative shaped by the method of survey using a questionnaire that measured using a five point likert scale. As for the samples taken amounted to 112 with non probability sampling and purposive sampling technique was used. Analytical techniques used is the multiple linear regression analysis. Obtained results are positive and significant influence between the endorser credibility and brand credibility against the loyalty of Yamaha motorcycle users. This shows the increasing endorser credibility and brand credibility will have an impact on increasing the loyalty of users of Yamaha motorcycles.   Keywords : endorser credibility, brand credibility, loyalty of user